Virtual reality for agribusiness: the development of a maintenance simulator for agricultural machinery for Senar Goiás - Figueredo, Vitor; Reis, Alessandro; Araújo, Fernando; Garcia, Fabiano (Anais do Simpósio de Realidade Virtual e Aumentada (SVR), 2019)
Simulators that employ virtual reality are already used as an educational resource for agribusiness. However, such innovation faces challenges particularly regarding content and the respective educational project. This article exposes a case study on a simulator designed to provide training for the maintenance of agricultural machinery. Developed by DOT digital group for Senar Goiás, the product was tested by nearly 200 people at an agribusinessfair in Goiás. The study concluded the following: a need to integrate content development with software development, the importance of extensive feedback for the target audience and prior planning of the evaluative and instructional aspects of the simulator.